2021
DOI: 10.1186/s12934-020-01503-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of overexpression of SNF1 on the transcriptional and metabolic landscape of baker’s yeast under freezing stress

Abstract: Background Freezing stress is the key factor that affecting the cell activity and fermentation performance of baker’s yeast in frozen dough production. Generally, cells protect themselves from injury and maintain metabolism by regulating gene expression and modulating metabolic patterns in stresses. The Snf1 protein kinase is an important regulator of yeast in response to stresses. In this study, we aim to study the role of the catalytic subunit of Snf1 protein kinase in the cell tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The serine/threonine protein kinase ( SNF1 expressed) is an important regulator of yeast in response to stress. Overexpression of SNF1 is effective in enhancing the cell tolerance and fermentation capacity of baker’s yeast in freezing, which may be related to the upregulated proteasome, altered metabolism of carbon sources and protectant molecules, and changed cell membrane components [ 38 , 39 ]. Ycp4p is predicted to be palmitoylated, a posttranslational modification typical of membrane-binding proteins involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…The serine/threonine protein kinase ( SNF1 expressed) is an important regulator of yeast in response to stress. Overexpression of SNF1 is effective in enhancing the cell tolerance and fermentation capacity of baker’s yeast in freezing, which may be related to the upregulated proteasome, altered metabolism of carbon sources and protectant molecules, and changed cell membrane components [ 38 , 39 ]. Ycp4p is predicted to be palmitoylated, a posttranslational modification typical of membrane-binding proteins involved in signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although its structure is well known, research on its various cellular regulatory mechanisms and their potential applications is ongoing. For example, the SNF1 complex has been applied to improve yeast cell resistance to various environmental stresses, improve lipid accumulation, improve leavening abilities, and so on [ 24 , 26 , 29 ]. In this study, the multiple effects of REG1 deletion combined with SNF1 overexpression were used to improve SAM production in S. cerevisiae , which provided a reference for the application of the SNF1 complex to abolish glucose repression and redirect carbon flux to nonethanol products in S. cerevisiae .…”
Section: Discussionmentioning
confidence: 99%
“…1 b) [ 23 , 27 ]. It was also reported that the overexpression of the SNF1 gene enhanced the responses to various environmental stresses, and the overexpression of SNF4 and the deletion of GLC7 or REG1 effectively enhanced maltose metabolism and leavening ability by ameliorating glucose repression in yeast [ 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in yeast the ATG autophagy pathway may collaborate with the SNF1 pathway to enhance survival under adverse environmental conditions, and inhibition of SNF1 would likely induce fungal degeneration over time [20]. Moreover, a contribution of Snf1 to yeast cell tolerance to freezing was also demonstrated [56].…”
Section: Other Roles Of the Snf1 Complex In Yeast And Filamentous Fungimentioning
confidence: 99%